2016
DOI: 10.1016/j.polymdegradstab.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of α-zirconium phosphate with hexachlorocyclotriphosphazene and its application in the flame retardant poly(vinyl alcohol) composites

Abstract: A planar-like inorganic α-zirconium phosphate (α-ZrP) particles were modified by a kind of cyclophosphazene derivative via three-step hybridization method, first modified by melamine (MA), then combined with hexachlorocyclotriphosphazene (HCCP) through nucleophilic substitution and further integrated with excessive MA. Thus, a hybrid flame retardant (HAC) was successfully synthesized. The composites based on poly(vinyl alcohol) (PVA) and HAC were prepared by solution blending. The thermal, mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…But the wide absorption ranges around 3200/cm for ─OH group almost disappear in HAPCP. At the same time, the two peaks at 523 and 601/cm for P─Cl group in HCCP are also disappeared in HAPCP. The almost disappearance of ─OH and P─Cl peaks indicates the reaction between ─OH and P─Cl groups.…”
Section: Resultsmentioning
confidence: 81%
“…But the wide absorption ranges around 3200/cm for ─OH group almost disappear in HAPCP. At the same time, the two peaks at 523 and 601/cm for P─Cl group in HCCP are also disappeared in HAPCP. The almost disappearance of ─OH and P─Cl peaks indicates the reaction between ─OH and P─Cl groups.…”
Section: Resultsmentioning
confidence: 81%
“…As can be seen, the peaks at 1604 and 1504 cm −1 correspond with the characteristic absorption of benzene ring appearing in REV and PRV. Banks at 862 and 963 cm −1 is ascribed to the P─N and P═N 20, stretching presented in HCCP and PRV. Furthermore, a new characteristic absorption peak appears at 1189 cm −1 (P─OPh), indicating that P─Cl on HCCP reacted with the hydroxyl group on REV.…”
Section: Resultsmentioning
confidence: 94%
“…The level of residue char graphitized is usually indicated by the I D /I G , the ratio of D band to the G band. In the combustion process, the high graphitization means a good effect to hinder mass and heat transfer, and the higher the ratio is, the higher the graphitization degree of carbon residue will be . As can be seen from Figure , the I D /I G value of pure EP is 2.49, and the I D /I G value of the EP composites is reduced to different degrees after the addition of different flame retardants.…”
Section: Resultsmentioning
confidence: 95%
“…Xu et al also synthesized functional α‐ZrP (HCA‐α‐ZrP) and prepared PVA composite by adding HCA‐α‐ZrP to polyvinyl alcohol (PVA). Their results showed that HCA‐α‐ZrP helps to reduce the fire hazard of PVA composite with an evident effect, and the LOI value of PVA composite added with 3 wt% HCA‐α‐ZrP reached 28.4% …”
Section: Introductionmentioning
confidence: 99%